Kajian Efektivitas Program Rehabilitasi sebagai Salah Satu Sektor Rencana Kerja Asean dalam Menangani Anak Penyalahguna Narkotika - Ahmad Fajar Satrio (PT Elaborium Elevasi Indonesia, 2023)
Currently, drug abuse by children continues to be a public concern and never stops being discussed and publicized. Certain circles, such as ASEAN (the Association of Southeast Asian Nations), have always been committed to fighting the threat of drugs in the Southeast Asian region. The main vision of the region is to achieve a